The Kathisma Church and Monastery of Mary Theotokos on the Jerusalem - Bethlehem Road - Avner, Rina. (Jerusalem)
ix, 321, [3] sayfa
Keywords: “This volume documents the excavations of the Kathisma church and monastery located on the ancient road from Jerusalem to Bethlehem. Kathisma is mentioned in Byzantine sources and pilgrimage itineraries, and identified as the holy place where Mary sat down to rest in her final stage of pregnancy before giving birth to Jesus. It played a role in the initial stages of Mary’s worship and its influence is still felt today.The octagonal church, built in the fifth century CE, is one of the most important discoveries of Early Christian architecture in the Holy Land in recent decades. The size of the church and its architectural plan, based on three concentric octagons, attest to it being designed as a pilgrimage church that could accommodate large audiences. In the Umayyad period, the church served both Muslim and Christian worshippers, as indicated by a miḥrab installed in the southern part, and the cancelation of the main apse by an Umayyad building. The splendid mosaics from this period in the southern rooms testify to artistic and iconographic influences of the wall mosaics in the Dome of the Rock. The evidence for the existence of a mosque in the Kathisma church constitutes the only archaeological evidence known to date for the ‘Covenants of ‘Umar’, which obliged Christians to relinquish areas in churches to Muslims“ -- Yayıncı.